NURSING CARE FOR PATIENTS UNDERGOING HEART SURGERY - Leal Nascimento, Mônica; Silva Oliveira, Geane; Sybelly Silva Matos, Gyanna; de Lira Silva, Macerlane (Health and Society, 2024)
INTRODUCTION: Nursing care for patients undergoing heart surgery is extremely important, as it is possible to avoid risks, as well as the manifestation of various complications. With regard to cardiac surgeries, surgical interventions have the possibility of reducing mortality and thus improving the quality of life of patients, as it favors the development and improvement of assistance itself. OBJECTIVE: To identify nursing care for patients undergoing cardiac surgery in the literature. METHODOLOGY: this study is an integrative review of the literature, based on the following guiding question: what is the nursing care provided to patients undergoing cardiac surgery? Data collection took place between the months of January and February 2024 through the databases Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Databases (BDENF), making use of the descriptors in health sciences (DeCS): nursing, cardiac surgery and patient. For the inclusion criteria, the following were adopted: articles published between the years 2019 and 2023, articles available in Portuguese for free, which addressed the topic and which were available in full, duplicate articles were excluded, that is, those present in more of a database, incomplete articles, and those that deviated from the study proposal. RESULTS AND DISCUSSIONS: It is worth noting that the postoperative period of cardiac surgeries, a period during which the patient recovers from post-anesthetic and post-surgical stress, is marked by the destabilization of the patient’s clinical condition, and is therefore , full of specificities, and critical care. Therefore, the postoperative period of cardiac surgery requires continued attention, resoluteness, and highly complex care from the nursing team. Therefore, it is possible to minimize various complications, such as changes in blood pressure levels, as well as compensation of organic systems. CONCLUSION: It is concluded, therefore, that the assistance of the nursing team to patients undergoing cardiac surgery is essential, as it makes it possible to carry out a continuous investigation, as well as to determine human responses, as well as to elaborate possible nursing diagnoses.